Radiotherapy for Non-Hodgkin’s lymphoma with cardiac infiltration: A case report - Wang, Weifeng; Zhang, Zhuo; Deng, Xiaocong; Gu, Anqi; Chen, Xianzhao; Cai, Yizheng; Zhao, Yuting (Frontiers in Oncology, 2023)
Background: Non-Hodgkin's lymphoma (NHL) with cardiac infiltration has a poor prognosis. The median OS of patients failing to respond to chemotherapy has been reported to be 1 month vs. 18 months in patients responding to chemotherapy. Case presentation: Herein, we reported a case of a 57-year-old male confirmed with diffuse large B-cell lymphoma who received radiation therapy of 150-cGy daily, administered in 30 fractions to the volume of cardiac infiltration, resulting in complete relief. Chemotherapy had no curative effect. The patient was subsequently enrolled in a clinical trial and received oral administration of zanubrutinib 80mg twice daily, after which he achieved complete remission. The progression-free survival was from diagnosis (January 7, 2020) to the follow-up (September 20, 2022), amounting to 32 months. Conclusion: Proper irradiation dose and timing of treatment can relieve NHL symptoms.